Crustacean Waste-Derived Chitosan: Antioxidant Properties and Future Perspective - Manikandan Muthu; Judy Gopal; Sechul Chun; Anna Jacintha Prameela Devadoss; Nazim Hasan; Iyyakkannu Sivanesan (MDPI AG, 2021)
Chitosan is obtained from chitin that in turn is recovered from marine crustacean wastes. The recovery methods and their varying types and the advantages of the recovery methods are briefly discussed. The bioactive properties of chitosan, which emphasize the unequivocal deliverables contained by this biopolymer, have been concisely presented. The variations of chitosan and its derivatives and their unique properties are discussed. The antioxidant properties of chitosan have been presented and the need for more work targeted towards harnessing the antioxidant property of chitosan has been emphasized. Some portions of the crustacean waste are being converted to chitosan; the possibility that all of the waste can be used for harnessing this versatile multifaceted product chitosan is projected in this review. The future of chitosan recovery from marine crustacean wastes and the need to improve in this area of research, through the inclusion of nanotechnological inputs have been listed under future perspective.